1995
DOI: 10.1021/bi00017a002
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Evidence for a Cysteine-Based Radical in Pyruvate Formate-lyase Inactivated with Mercaptopyruvate

Abstract: Pyruvate formate-lyase (PFL) is a glycyl radical-containing enzyme that catalyzes the reversible, nonoxidative conversion of pyruvate and CoA into acetyl-CoA and formate. The radical is located on the alpha-carbon of glycine 734 and is required for catalysis. Two cysteine residues, C418 and C419, are also essential for catalysis. Mercaptopyruvate, a biologically relevant pyruvate analog, is shown here to be a mechanism-based inactivator of PFL. Upon addition of mercaptopyruvate to active PFL, an EPR spectrum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…In support of such a model are the facts that the E. coli anaerobic ribonucleotide reductase has been observed to be inhibited by class I and class II mechanism-based inhibitors (34) and that the k cat of 3 s Ϫ1 obtained in this study for the T4 anaerobic reductase closely matches the k cat of 4 -11 s Ϫ1 found for the E. coli class I enzyme (30,39,40). Recently, the pyruvate formatelyase enzyme has been identified to contain a thiyl radical at its active site (41). We are currently investigating the role of conserved cysteine residues as potential members of an anaerobic ribonucleotide reductase active site that would be homologous to the active site cysteines in the aerobic class I reductase.…”
Section: Discussionsupporting
confidence: 79%
“…In support of such a model are the facts that the E. coli anaerobic ribonucleotide reductase has been observed to be inhibited by class I and class II mechanism-based inhibitors (34) and that the k cat of 3 s Ϫ1 obtained in this study for the T4 anaerobic reductase closely matches the k cat of 4 -11 s Ϫ1 found for the E. coli class I enzyme (30,39,40). Recently, the pyruvate formatelyase enzyme has been identified to contain a thiyl radical at its active site (41). We are currently investigating the role of conserved cysteine residues as potential members of an anaerobic ribonucleotide reductase active site that would be homologous to the active site cysteines in the aerobic class I reductase.…”
Section: Discussionsupporting
confidence: 79%
“…The powder pattern is dominated by an axially asymmetric g anisotropy with principal values of g 1 ϭ 2.023, g 2 ϭ 2.015, and g 3 ϭ 2.002. These g values eliminate a thiyl radical (28)(29)(30) and a persulfide radical (28,36,37) as the source of this signal and are consistent with a disulfide radical anion (Table 1) (28,(38)(39)(40). Finally, we also note in the low-field edge of the spectrum a long, weak tail (Fig.…”
supporting
confidence: 80%
“…In pyruvate formate lyase a disulfide radical is formed when the enzyme is inactivated with mercaptopyruvate, and a sulfinyl (and a peroxyl) radical is formed when pyruvate formate lyase is inactivated in the presence of oxygen (21,22). The disulfide radical has g x ϭ 2.057, g y ϭ 2.023, g z Ϸ 2.00, and the sulfinyl radical has g x ϭ 2.0204, g y ϭ 2.0084, g z ϭ 2.0005.…”
Section: Discussionmentioning
confidence: 99%